الجملة الخبرية في أشعار الأحاجي النحوية ( دراسة دلالية ) - عبد الله خلف, نهلة; صالح باقر, علي (Journal of College of Education, 2019)
This research sheds light on the poetry of grammatical arguments, which the reader thinks - perhaps just a thought - that they are words paved, they are made by making the puzzle only, but when we read it several times we found otherwise in most of them, as most of them return to ancient poets, They were an example to be followed, and a source of martyrdom, including Farazdak, Jarir, and others, and this argument to take advantage of the implied significance of the news, and this research will show the semantic news that came out poems poems grammar